Does steatosis affect the performance of diffusion-weighted MRI values for fibrosis evaluation in patients with chronic hepatitis C genotype 4? - Besheer, Tarek; Razek, Ahmed Abdel Khalek Abdel; El-Bendary, Mahmoud; El-Maksoud, Mohamed Abd; Elalfy, Hatem; Zalata, Khaled; Elkashef, Wagdi; Zaghloul, Hosam; El-Gilany, Abdel-Hady (Turkish Journal of Gastroenterology, 2017)
Abstract Background/Aims: To evaluate the effect of hepatic steatosis on the apparent diffusion coefficient (ADC) of hepatic fibrosis in patients with HCV genotype 4-related chronic hepatitis. Materials and Methods: Overall, 268 chronic hepatitis C patients (164 males and 104 females) underwent liver biopsy for fibrosis assessment by the METAVIR score and grading for hepatic steatosis. They were classified into early fibrosis stage (F1, F2) and advanced fibrosis stage (F3, F4). Diffusion-weighted MRI (DWI) of the liver was performed using 1.5-Tesla scanners, and the ADC value of the patients with and without steatosis in different stages of fibrosis was estimated and compared. Results: In patients with early fibrosis, the ADC value significantly decreased in patients with steatosis (1.52±0.17×10-3 mm2/s) compared to that in patients without steatosis (1.65±0.11×10-3 mm2/s) (p<0.001). In those with an advanced stage of fibrosis, the ADC value was also significantly decreased in patients with steatosis (1.07±0.16×10-3 mm2/s) compared with that in patients without steatosis (1.35±0.11×10-3 mm2/s) (p≤0.001). The cutoff value for ADC for steatosis prediction in the early fibrosis group was 1.585 according to the AUROC curve, with a sensitivity of 76.8% and a specificity of 73.5%. The cutoff value for ADC for steatosis prediction in patients with an advanced stage of fibrosis was 1.17×10-3 mm2/s, with a sensitivity of 97% and a specificity of 88.5% Conclusion: Histologically detected hepatic steatosis should always be considered when assessing hepatic fibrosis using diffusion-weighted MRI to avoid the underestimation of the ADC value in patients with chronic hepatitis C genotype 4. Cite this article as: Besheer T, Abdel Razek AA, El-Bendary M, et al. Does steatosis affect the performance of diffusion-weighted MRI values for fibrosis evaluation in patients with chronic hepatitis C genotype 4? Turk J Gastroenterol 2017; 28: 283-8.